2022
DOI: 10.1021/acsmaterialsau.1c00072
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystalline Germanium Nanocrystals via a Two-Step Microwave-Assisted Colloidal Synthesis from GeI4

Abstract: Colloidal germanium (Ge) nanocrystals (NCs) are of great interest with possible applications for photovoltaics and near-IR detectors. In many examples of colloidal reactions, Ge­(II) precursors are employed, and NCs of diameter ∼3–10 nm have been prepared. Herein, we employed a two-step microwave-assisted reduction of GeI4 in oleylamine (OAm) to prepare monodispersed Ge NCs with a size of 18.9 ± 1.84 nm. More importantly, the as-synthesized Ge NCs showed high crystallinity with single-crystal nature as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As the Si content increases, the contrast between QDs and carbon background decreases, due to mass of Si being much closer to carbon than Ge or Sn. It was also found that the Ge 1– x – y Si y Sn x QDs are colloidally stable in nonpolar solvents because of surface passivation by OLA and ODE ligands (Supporting Information, Figure S5) . It is also possible that there are some residual butyl groups on the surface from n -BuLi used during the synthesis, which can further contribute to nonpolar surface passivation.…”
Section: Resultsmentioning
confidence: 99%
“…As the Si content increases, the contrast between QDs and carbon background decreases, due to mass of Si being much closer to carbon than Ge or Sn. It was also found that the Ge 1– x – y Si y Sn x QDs are colloidally stable in nonpolar solvents because of surface passivation by OLA and ODE ligands (Supporting Information, Figure S5) . It is also possible that there are some residual butyl groups on the surface from n -BuLi used during the synthesis, which can further contribute to nonpolar surface passivation.…”
Section: Resultsmentioning
confidence: 99%
“…The first three electron diffraction rings were attributed to the (111), (220), and (311) crystal planes of Ge, which were in consistence with the results reported in previous studies. 17,29 The concentric electron diffraction rings in Figure 2d indicate the polycrystalline nature of Ge. The TEM results for Ge@C-1 and Ge@C-3 also testified to verify the differences among the Ge@C-X composites (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the carbon material with benign mechanical properties would provide a buffer layer for the volume change of the electrode and improve the charge transfer during the electrochemical process. ,, Meanwhile, a stable SEI layer can be formed on the surface of the carbon materials to control the electrolyte reduction. Since a carbon resource was essential for the performance of the Ge-based electrode, tuning the properties of the carbon matrix was identified as one of the most useful and practical methods. , Doping of the carbon skeleton with heteroatoms such as nitrogen (N), phosphorus (P), and sulfur (S) was proved to be beneficial for the electron transfer and increase in energy density . Among these heteroatoms, N-doping has been widely studied and N atoms served as electron donors, resulting in a high electronegativity in the N-doped region.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor nanoparticles (NPs) are NPs whose optical properties are adjustable, from UV to IR, via quantum confinement and according to the semiconductor material used. For several years, the interest in these NPs has strongly increased with, for example, their integration in the development of the third generation of solar cells . These materials can also find applications in infrared optoelectronics, where sources such as detectors remain expensive and where current technologies present few prospects for massive cost reductions .…”
Section: Introductionmentioning
confidence: 99%
“…For several years, the interest in these NPs has strongly increased with, for example, their integration in the development of the third generation of solar cells. 4 These materials can also find applications in infrared optoelectronics, where sources such as detectors remain expensive and where current technologies present few prospects for massive cost reductions. 5 Works recently carried out by several researchers show that NP technology can present a novel, very low-cost sector for photovoltaic detection and photodetection.…”
Section: ■ Introductionmentioning
confidence: 99%